La Acción de Protección como mecanismo de garantía de los derechos: configuración institucional, práctica y resultados - José Luis Castro Montero; Luis Santiago Llanos Escobar; Pablo Sebastián Valdivieso Kastner; Wladimir García Vinueza (Universidad Hemisferios, 2016)
Since 2008, the Ecuadorian Constitution introduced several changes in the institutional layout of constitutional mechanisms intended to protect fundamental rights. The present work analyzes protective action (PA) —acción de protección—, a constitutional guarantee which was created to safeguard and protect constitutional rights against acts or omissions of non-judicial public authorities or non-public actors. In absence of empirical evidence about how the PA works, this study evaluates its performance through a quantitative analysis of an original database. Thus, this study explores the operation of the PA in Quito, covering first instance and appellate court decisions, issued between November 2008 and June 2014. Then, patterns in the resolution of this constitutional guarantee are described. The results show a limited performance of the PA, as it is insufficient to guarantee and repair fundamental rights, mainly when the state acts as the defendant.